Pengaruh Loan to Deposit Ration dan Return On Asset Terhadap Dividen Perusahaan Perbankan Pada Bursa Efek Indonesia Periode 2016-2020 - Diana Gustinya, SE., M.Ak. (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2022)
The research was conductedto determine the effect Loan of Deposit Ration, Return On Asset to individual banking firm Indonesin stock exchange ( IDX) priod 2016-2020. This research uses quantitative statistical data of banking companies, literature, financial report published by banks or the internet that have ben audited by banking companies on the Indonesia Stock Exchange (IDX), in order to obtain an overview of the bank. The result of this study indicate that the Loan to Deposit Ration, Return On Assets and devidends are partially respectively. Loan to Deposit Ration has insignificant and negative effect on devidends. This can be explained by the Loan to Deposit Ratio t value of 1.889 with a propability level of 0.064 which is smaller tahn 0.05. Return on assets (ROA) has asignificant and positive effect on devidends. This can explained by the t count value of 1.889 with a probability level of 0.0064 grater than 0.05. Loan to Deposit Ration (LDR) and Return On Assets (ROA) simultaneously on devidends have a moderate effect of 0.501. The amount of contribution Requare or the coefficientof determinarion is 0.251, which means that the Loan to Deposit Ratio (LDR) and Return On Assets (ROA) variable contribute 25.1% to devidends. While the remaining 74.9 %is influenced by other variables.